Healthy eating habits for food industry in Portugal - Lopes da Costa, R.; Miguel, I.; Pereira, L.; Dias, Á.; Gonçalves, R. (Revista Portuguesa de Estudos Regionais, 2023)
The changes in the eating habits are leading to and increase interest by the consumers regarding organic food making important to understand how consumers see these products and what are the main drivers behind their decision to consume them or not and how the market of organic food can provide an offer that can provide and sustainable growth. The focus of this investigation was to understand the opinion of the Portuguese consumers in relation to organic foods. To achieve this the research uses descriptive and content analysis to drive results from a sample of 282 questionnaires and 15 interviews. The results showed that the implication that organic food can have in health is the main factor for consumers to choose to buy and consume this type of food and that high prices is the main barrier for not consuming it. The insights provide by this study will give managers of this sector a understanding of the consumers expectations and thar will how to define better strategies to assure a sustainable organizational growth.